Endosulfan poisoning: An overview. (October 2017) - Menezes, Ritesh G.; Qadir, Tooba Fatima; Moin, Ariba; Fatima, Huda; Hussain, Syed Ather; Madadin, Mohammed; Pasha, Syed Bilal; Al Rubaish, Fatima A.; Senthilkumaran, S.
Abstract: Endosulfan, an organochlorine (OC) insecticide, is a widely used agricultural pesticide, despite its life threatening toxic effects. In this review, the pharmacokinetics of endosulfan, mechanism of endosulfan toxicity, clinical presentations and management, histopathological findings, and toxicological analysis are described, in addition to its environmental toxicity. The toxic effects of endosulfan can affect many organs and systems presenting in a wide array of signs and symptoms. Although termed a restricted OC-classed pesticide, it continues to be used, especially in the developing world, owing to its beneficial effects on agriculture. Several cases of endosulfan poisoning have been reported from different regions of the world. Whether accidental or intentional, endosulfan ingestion proves to be fatal unless immediate, aggressive treatment is initiated. Management is mainly supportive as no antidote exists for endosulfan poisoning as yet. The use of endosulfan needs to be strictly regulated and eventually banned worldwide altogether to lower the current morbidity and mortality resulting from this pesticide. Additionally, monitoring biological samples, using non-invasive techniques such as breast milk sampling, can provide an effective method of observing the elimination of this environmentally persistent organic pollutant from the general population. Highlights: This article is a brief overview on endosulfan poisoning related to human toxicology. Endosulfan is a restricted organochlorine-classed pesticide. Endosulfan continues to be used as an agricultural pesticide. Endosulfan is classified as a 'persistent organic pollutant'. Endosulfan remains in the environment for extended periods of time.